Advanced imaging for risk stratification of sudden death in hypertrophic cardiomyopathy. Issue 11 (16th January 2020) - Ramchand, Jay; Fava, Agostina M; Chetrit, Michael; Desai, Milind Y
Abstract : Hypertrophic cardiomyopathy (HCM) is a common inherited cardiac condition, which typically manifests as left ventricular hypertrophy. A small subset of patients with HCM have an increased risk of sudden cardiac death (SCD) from ventricular arrhythmias. Risk of SCD can be effectively reduced following implantation of implantable cardiac defibrillators (ICD), although this treatment carries a risk of complications such as inappropriate shocks. With this in mind, we turn to advances in cardiac imaging to guide risk stratification for SCD and to select the appropriate individual who may benefit from ICD implantation. In this review, we have taken the opportunity to briefly summarise the role of imaging in the diagnosis of HCM before focusing on how specific imaging features influence risk of SCD in patients with HCM.